Tricarbonylchlorido(η(5)-cyclopentadienyl)molybdenum(II) - Ogweno, Aloice O. (International Union of Crystallography, 2012)
The structure of the title compound, [Mo(C(5)H(5))Cl(CO)(3)], reveals a pseudo-square-pyramidal piano-stool coordination around the Mo(II) ion, which is surrounded by a cyclopentadienyl ring, three carbonyl groups and a chloride ligand.